Electrospun Polyacrylonitrile-Based Scaffolds Reinforced with Argopecten Purpuratus-Derived Cao for Enhanced Biomedical Functionality - Garcia-Herrera, C (American Chemical Society, 2025)
Electrospun nanofiber scaffolds are widely explored for biomedical applications, because of their high porosity and ability to mimic the extracellular matrix. However, synthetic polymers like polyacrylonitrile (PAN), while biocompatible, often require functional enhancement to improve their bioactivity and wound healing capacity. The incorporation of nanoparticles, especially those derived from waste, such as calcium oxide (CaO) from sustainable sources, has been shown to improve the properties of polymer matrices for various biomedical applications. In this study, calcium oxide nanoparticles (n-CaO) derived from Argopecten purpuratus shell waste (18.5 ± 4.5 nm) were incorporated into PAN at 5, 10, and 20 wt % by electrospinning, aiming to develop a sustainable and functional scaffold for tissue engineering and wound healing. The PAN and PAN/CaO matrices were characterized, revealing significant improvement in hydrophilicity and mechanical stability upon CaO incorporation. In vitro studies demonstrated bioactivity through the formation of hydroxyapatite layers and confirmed biocompatibility with human fetal osteoblasts and dermal fibroblasts, along with enhanced cell migration and wound closure rates. In vivo subdermal implantation in BALB/c mice confirmed the biocompatibility of the scaffolds, showing advanced healing and fibrovascular tissue formation. Our result suggested that PAN/CaO with 10 wt % of CaO showed better promise for engineering and wound healing therapies due to its morphological, mechanical, bioactive, and biological parameters for their possible applications. These findings suggest that the combination of waste-derived PAN and n-CaO is a promising and environmentally friendly candidate for applications in tissue engineering and wound healing. © 2025 American Chemical Society